2020
DOI: 10.1186/s12966-020-01008-4
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide surveillance of self-reported sitting time: a scoping review

Abstract: Background: Prolonged sitting time is a risk factor for chronic disease, yet recent global surveillance is not well described. The aims were to clarify: (i) the countries that have collected country-level data on self-reported sitting time; (ii) the single-item tools used to collect these data; and (iii) the duration of sitting time reported across lowto high-income countries. Methods: Country-level data collected within the last 10 years using single-item self-report were included. The sixstage methodology: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 31 publications
1
45
2
1
Order By: Relevance
“…These unique determinants/macrolevel drivers and potential differential health impacts of sedentary behaviour require more detailed data and understanding across a wider range of countries, with a focus on disadvantaged populations and LMICs. Recent global surveillance data, though somewhat limited, indicates that self-reported sedentary time varies substantially between high- and low-income countries [ 59 ], with high-income countries reported sedentary time almost double that of low income countries (4.9 vs 2.7 h/day). Moreover, the contextual patterns in which sedentary behaviours occur also vary by indices of socioeconomic status and markers of social disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…These unique determinants/macrolevel drivers and potential differential health impacts of sedentary behaviour require more detailed data and understanding across a wider range of countries, with a focus on disadvantaged populations and LMICs. Recent global surveillance data, though somewhat limited, indicates that self-reported sedentary time varies substantially between high- and low-income countries [ 59 ], with high-income countries reported sedentary time almost double that of low income countries (4.9 vs 2.7 h/day). Moreover, the contextual patterns in which sedentary behaviours occur also vary by indices of socioeconomic status and markers of social disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…A study reporting the median hours per day of sitting time indicated that people from upper-middle income countries spent on average 234 minutes per day [ 36 ]. This result was slightly higher compared to the one obtained in our study (214.7 minutes per day) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the participants before the intervention showed a highly sedentary behavior (~8.8 h), and this behavior remained unchanged after 10-weeks of the virtual PA program; although, the volume of PA prescribed met the recommendations by the American College of Sports and Medicine during COVID-19 [34,35]. Furthermore, before the intervention, the sitting time (3.8 h/day) was similar to what was reported in an upper-middle income country (3.9 h/day) and by the end of the program was higher compared to high-income countries (4.7 h/day) [36].…”
Section: Discussionmentioning
confidence: 61%